1999
DOI: 10.3354/cr013001
|View full text |Cite
|
Sign up to set email alerts
|

Climate and mortality in Australia: retrospective study, 1979-1990, and predicted impacts in five major cities in 2030

Abstract: Quantitative assessment of climatic and environmental health risks is necessary because changes in climate are expected. We therefore aimed to quantify the relationship between climatic extremes and mortality in the 5 largest Australian cities during the period [1979][1980][1981][1982][1983][1984][1985][1986][1987][1988][1989][1990]. We then applied the relationship determined between recent climatic conditions and mortality to scenarios for climate and demographic change, to predict potential impacts on publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 18 publications
1
109
1
1
Order By: Relevance
“…Because of the extremely large differences in population between regions, they were grouped in 54 larger and more homogeneously populated areas. A transfer function (also referred here as temperature/mortality or T/M relationship) was estimated for the period with available observations (1998)(1999)(2000)(2001)(2002)(2003), and used to convert simulated daily temperatures from other periods into daily mortality projections 15,26,27 . The transfer function is separately adjusted to data above (warm tail) and below (cold tail) the temperature of minimum mortality, or comfort temperature 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Because of the extremely large differences in population between regions, they were grouped in 54 larger and more homogeneously populated areas. A transfer function (also referred here as temperature/mortality or T/M relationship) was estimated for the period with available observations (1998)(1999)(2000)(2001)(2002)(2003), and used to convert simulated daily temperatures from other periods into daily mortality projections 15,26,27 . The transfer function is separately adjusted to data above (warm tail) and below (cold tail) the temperature of minimum mortality, or comfort temperature 15 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, Guest et al (1999) noted that future mortality impacts in Australia's 5 largest cities would be small by 2030. McGregor et al (2004) found that years with strong temperature seasonality also exhibited elevated mortality from ischaemic heart disease in 5 English counties.…”
Section: Discussionmentioning
confidence: 99%
“…Given the general sensitivity of death and illness to temperature (West 1973, Bull & Morton 1975, Auliciems & Frost 1989, Auliciems & Skinner 1989, McKee 1990, Frost et al 1992, Frost 1993, Guest et al 1999, Laschewski & Jendritzky 2002, diseases such as IHD may be potentially predictable. The purpose of this paper is therefore to undertake an exploratory analysis of the statistical association between the seasonality of temperature and IHD mortality for 5 English counties as a basis for investigating the potential predictability of the magnitude and timing of the annual IHD mortality peak.…”
Section: Introductionmentioning
confidence: 99%